Hemifacial Trigeminal Pain Referred from Occipital Neuralgia Due to Compression of the Greater Occipital Nerve by the Occipital Artery - Ko, Hak-cheol; Choi, Jin-gyu; Son, Byung-chul (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Although pathologic vascular contact between the occipital artery and the greater occipital nerve (GON) at the crossing point in the nuchal subcutaneous layer can cause occipital neuralgia, referred hemifacial trigeminal pain from chronic occipital neuralgia owing to this cause is extremely rare.A 61-year-old female patient with left-sided occipital neuralgia for 4 years presented with a new onset of left-sided hemifacial pain. Decompression of the left GON from pathologic contacts with the occipital artery resulted in immediate relief for hemifacial pain and chronic occipital neuralgia. The present case implies that sensitization and hyperactivity of the trigeminocervical complex that receives the convergent input from trigeminal and high cervical occipital nociceptive pathways can be a pathogenic mechanism in referred hemifacial pain from occipital neuralgia. In the present case, a branching tributary of the occipital artery at the crossing point forming a constricting loop above the course of the GON was found to be the cause of entrapment. Because the occipital artery is reported to be consistently located superficial to the GON at the crossing point, a spatial relationship between the occipital artery and the GON rather than a mere adhesion or contact might have pathologic significance in the development of occipital neuralgia.
Keywords: greater occipital nerve; occipital artery; occipital neuralgia; surgical decompression; trigeminocervical complex